Authoritarian Resilience Versus Everyday Resistance: The Unexpected Strength of Religious Advocacy in Promoting Transnational Activism in China. Issue 3 (8th January 2018) - Wang, Ray
Abstract: This article examines one of the most sensitive forms of transnational activism—the money and services foreign advocacy groups provide to empower locals—and explores the reasons why some aid groups have been allowed to work in certain locations when conventional wisdom and experience would indicate otherwise. In a careful comparison of four Chinese cities with similar geographic, political, and economic conditions, we find that only one particular form of religious activist network has been tolerated and its rule‐breaking nature has created a persistent activism of "everyday resistance." Thus, decoding the mechanisms of its success, named "backdoor listing" and "minority‐majority alliance, " can help to expand our knowledge about not only the possibility of religious freedom in China, but also our theoretical understanding of the transnational activism strategies that are being widely debated and employed to improve human rights worldwide.